MATERIAL FLOW ANALYSIS OF ALUMINIUM IN A DYNAMIC SYSTEM: JERAM SANITARY LANDFILL - P., Agamuthu; M. S., Venu Mahendra; M., Mohd Afzanizam (Malaysian Journal of Science, 2011)
Jeram Sanitary Landfill (JSL) receives waste from seven major municipalities, mostly from Kuala Lumpur and Selangor Municipality. The types of waste received are domestic waste, bulky waste and garden waste only. Currently, an average of 2100 tonne of solid waste per day from 470 compactors were landfilled daily at JSL. Each compactor disposed 4.6 tonnes which gives estimated at 766,500 tonnes in 2010. Out of this amount, 9.25 tonnes of Al end up in landfill per year. Most of the aluminum can are sent for recycling with approximately 1.39 tonnes/day. The leaching quantified through both gas and leachate was at 0.42 tonnes/day and 0.14 tonnes/day respectively. From the gas leaching, about 0.34 tonnes/day was released from the soil while 0.12 tonnes/day escaped through evaporation. Al in soil was quantified highest at near surface. This was identified as sink of the whole Al system. A major problem of sanitary landfill is the assessment of element transfers from inputs to outputs as a function of time due to the dynamic nature of the landfill activities. (Keywords: Aluminium, Jeram landfill, Solid Waste Composition, Material Flow)